Improving throughput of a semi-automated assembly line subject to operator skill-level constraint - See, Shu Xin (2022)
Integrating humans into manufacturing systems has been considered a critical aspect in a semi-automated line as dynamic human characteristic constrains the throughput production and leading to the occurrence of manufacturing bottleneck. In the research, it is discovered that the manufacturing problems was incurred at the manual assembly workstation where the process has longest cycle time and lowest production output.With regards to this, this paper presents a methodology for analysis of the bottleneck in the manufacturing systems and aims to develop potential solutions that have direct impact toward throughput improvement. Results obtained are based on the research that was carried out in the Camfil Malaysia Sdn Bhd. In this research, Root Cause Analysis was implemented as an analytical technique and preliminary step to identify the potential causes of the manufacturing problems. It was found out that poor arrangement of tasks, inconsistent performance of operators, imbalance in workload distribution, poor workflow and poor layout design were the main issues encountered in the manual bottleneck workstation. To tackle the relevant production issues, work standardization, 5s practices and redesign facility layout were adopted in the manufacturing line. Besides, Kaizen was applied in re-constructing the work sequence, working technique, equipment, work scheduling, workflow and the design layout.